2012
DOI: 10.1371/annotation/230240bc-bcf3-46b2-9b21-2e6e584f7333
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Multidrug Resistant Pulmonary Tuberculosis Treatment Regimens and Patient Outcomes: An Individual Patient Data Meta-analysis of 9,153 Patients

Abstract: Background: Treatment of multidrug resistant tuberculosis (MDR-TB) is lengthy, toxic, expensive, and has generally poor outcomes. We undertook an individual patient data meta-analysis to assess the impact on outcomes of the type, number, and duration of drugs used to treat MDR-TB.Methods and Findings: Three recent systematic reviews were used to identify studies reporting treatment outcomes of microbiologically confirmed MDR-TB. Study authors were contacted to solicit individual patient data including clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…[19][20][21] In a recent individual patient data meta-analysis of 9,153 patients, the pooled treatment success was only 54% (95% CI = 53-55%). 22 In that study, treatment success was associated with use of later-generation quinolones, ethionamide, or prothionamide, use of four or more likely effective drugs in the initial intensive phase, and use of three or more likely effective drugs in the continuation phase. In addition, the greatest odds of success were seen in patients who had 7.0-8.5 months for the intensive phase and a total length of treatment of 24.6-27.5 months.…”
Section: Discussionmentioning
confidence: 96%
“…[19][20][21] In a recent individual patient data meta-analysis of 9,153 patients, the pooled treatment success was only 54% (95% CI = 53-55%). 22 In that study, treatment success was associated with use of later-generation quinolones, ethionamide, or prothionamide, use of four or more likely effective drugs in the initial intensive phase, and use of three or more likely effective drugs in the continuation phase. In addition, the greatest odds of success were seen in patients who had 7.0-8.5 months for the intensive phase and a total length of treatment of 24.6-27.5 months.…”
Section: Discussionmentioning
confidence: 96%
“…These restrictions come mainly from the already-cited individual patient data meta-analysis showing a higher risk of treatment failure and relapse in patients with such strains compared to susceptible strains [36]. Interestingly, a previous individual meta-analysis showed that the inclusion of ethionamide/prothionamide as well as a longer use of injectables in the regimen were associated with treatment success; clofazimine, now considered as an important companion drug, was found not to have significant activity [5]. Several issues arise from the manner in which such meta-analyses were performed, as these assess the efficacy of individual drugs, neglecting the regimen in which individual drugs were used.…”
Section: Discussionmentioning
confidence: 99%
“…The overall treatment success was 48%; 10% had treatment failure; and 28% were lost to follow-up [4]. The same year (2012), an analysis of individual patient data showed very similar results [5]. Toxicity, long duration, and high costs were identified as causes of poor outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant tuberculosis (MDR-TB), which is caused by Mycobacterium tuberculosis strains that are resistant to both isoniazid and rifampin, is a large public health threat. The majority of MDR-TB cases have unsatisfactory outcomes; there is a treatment success rate of approximately 60% despite the use of second-line anti-TB drugs for 18–24 months [1,2]. Historically, MDR-TB treatment response is monitored by microbiological examination of sputum-negative culture conversion [3].…”
Section: Introductionmentioning
confidence: 99%